Identifikasi Mikroplastik di Sungai Ngrowo, Tulungagung - Kartikasari, Desi; Zunisnaini, Zunisnaini; Nurdianyoto, Indra (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
Microplastics are synthetic organic polymers with size range 0.001-5 mm. The existance of microplastics disperse in the environment are harmful to human and natural ecosystems along with possess damage effects on aquatic organisms. The aim of the research was to determine types and abundance of microplastics in Ngrowo River Tulungagung. Sampling of microplastics was conducted at three locations, namely north city, center city and south city. The stages of the research were start from abiotic factors measurement of water continued with sampling, filtering and drying sample, purifying and separation of microplastics particle and observation using stereo microscope. The microplastics types found were fragment, fiber, filament, granule and foam with the highest average of abundance 13,450 particles.(m3)-1 at the center city. The colors of microplastics obtained were dark blue, transparent, chocolate, white, black, grey and red with the highest number was dark blue. Microplastics are known derived from run off road the plastic particle, plastic degradation of domestic waste, industry and others anthropogenic activities.